Evaluasi Kinerja Simpang dengan Alat Pemberi Isyarat Lalu Lintas (APILL) di Kota Malang - Galih Damar Pandulu; Zeliana Fatima Da Silva; M Sa'dillah (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
There are methods to measure the performance of intersections, including the 1997 Indonesian Road Capacity Manual and the 2014 Indonesian Road Capacity Manual. The 2014 Indonesian Road Capacity Guideline (PKJI 2014) is a form of updating from the 1997 MKJI. The purpose of this study is to determine the existing conditions at the intersection of Sumbersari road - Veteran road - Bendungan Sutami road - Sigura-gura road at Malang City to generate traffic signals on the intersection. From the results of the analysis of the time phase change solutions that have been carried out, the results obtained for calculating the performance of signaled deposits with the degree of saturation known as Sumber Sari road of 0.78 (Service level D), Bendungan Sutami road of 1.50 (F service level), Veteran road is 2.28 (Service level F) and Sigura-gura road is 0.32 (Service level B). The level of service at the intersection is still less than optimal, where the delay for each arm exceeds the specified limit exceeding the standard 60 seconds/skr.